Hybrid Dryer of Cassava Chips. Issue 1 (May 2021) - Warji, W; Tamrin, T
Abstract: Hybrid type dryer is a dryer whose energy source comes from solar energy and additional gas, electricity or biomass energy. This dryer has transparent walls and is closed so that the sun's heat can enter the drying room, but rain cannot enter the drying room. This dryer is equipped with a fan that serves to push the heat so that it spreads throughout the drying room. This dryer is equipped with an exhous fan so that moisture is sucked out of the drying chamber. The main source of drying energy comes from solar energy, when the drying cloud is assisted by additional energy and when it rains the main drying energy comes from biogas combustion energy. The hot air flow control slot is designed in the drying chamber so that hot air can flow between the heating racks. The average air temperature in the chamber are 44.5 °C, 47.3 °C and 56.3 °C with heating sources of solar energy, electricity and solar energy with electrical, respectively. Cassava chips can be dried in a hybrid dryer. The initial moisture content of 60% decrease to 10%-12% wet basis. Drying chips using solar energy requires 18 hours of drying, for 16 hours using electrical energy, and 12 using a hybrid of solar energy with electrical energy.